Death and other occupational hazards : a novel - Dapunt, Veronika (Poisoned Pen Press, 2026)
"Her job is to die for. Literally. Most people think that when they meet Death, it'll be a skeleton in a black potato sack. Maybe with a scythe. Truth is, she's just a woman doing a job, and she's very good at it. But when Death takes a much-needed break to live on earth, things start to go terribly wrong. Someone's killing people not on her list (well, not yet anyway) and it's down to her to find the culprit before it's too late. To make matters worse, her sanctimonious sister, Life - whom Death hasn't got on with in millennia - won't stop blaming her . . . And then there's the slight problem of the charming (sexy) parasitologist she's suspicious of. But she'll be fine, right? After all, who better to investigate a murder than Death herself?"-- Provided by publisher.